An Analysis of the Influence of Discounts, Promotions, and Consumer Trust on Purchasing Decisions of Shopee Application Users (Case study of Management Study Program Students Class of 2021, Mandalika Education University) - Sulaeman, Sulaeman; Mujriah, Mujriah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research was conducted to find out how much influence Discounts, Promotions and Consumer Trust have on Purchasing Decisions among Shopee Application Users among students at the Mandalika University of Education Management Study Program Class of 2021. This research uses multiple linear regression analysis methods to verify the influence of Discounts, Promotions and Consumer Trust which influence Mandalika Education University students' decisions in purchasing products on the Shopee application. The data used is primary data obtained from distributing questionnaires to 60 respondents. The results of this research show that there is a significant positive influence of discounts on purchasing decisions for Mandalika Education University students who use the Shopee application. There is a significant positive influence of promotion on purchasing decisions for Mandalika Education University students who use the Shopee application. There is a significant positive influence of Consumer Trust on purchasing decisions among Mandalika Education University students who use the Shopee application. There is a simultaneous significant positive influence of discounts, promotions and consumer trust on purchasing decisions among Mandalika University of Education Management Study Program Class of 2021 students who use the Shopee application.